Penatalaksanaan Fisioterapi pada Kasus Calcaneus Spur Dextra dengan Modalitas Ultrasound, Hold Rilex dan Calf Raise di RSUD Ciereng Subang - Sita Dewi Lestari; Ika Rahman (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Calcaneus spur is an abnormal bone growth on the inferior part of the os. calcaneus, from the fibrocartilaginous attachment site specifically the plantar fascia ligament, which is a common cause of calcaneus spur. To determine the physiotherapy management in reducing pain, increasing joint range of motion and increasing functional activity ability in Calcaneus Spur Dextra cases with ultrasound, hold rilex and calf raise modalities. After 6 times of therapy using VAS, it shows a decrease in silent pain T1 worth 2 to T6 worth 0, a decrease in motion pain T1 worth 5 to T6 worth 2 and a decrease in tenderness T1 worth 6 to T6 worth 3. Increased active motion LGS in the sagittal plane dextra ankle joint T1: 100- 00- 300 to T6: 200-00-400. Increased functional activity ability which can be seen from the increase in FADI score T1 worth 76% to T6 worth 87% with moderate difficulty. Ultrasound can help reduce pain, hold rilex and calf raise can help increase joint range of motion and improve functional activity ability.